An influence of wall structure on acoustic pressure distribution in a operator’s cabin - Michałowski, S.; Stolarski, B.; Dziechciowski, Z. (Archives of Acoustics, 2006)
Acoustic conditions in operator’s cabin may be formed by using parameters of the cabinwall structure. It might be carried out by changing properties of wall components. This paperpresents results of simulation which aim was the assessment of acoustic conditions in aoperator’s cabin under influence of changes wall structure parameters.